111In-DOTA-Annexin V for imaging of apoptosis during HSV1-tk/GCV prodrug activation gene therapy in mice with NG4TL4 sarcoma. (February 2016) - Lin, Ming-Hsien; Wu, Shih-Yen; Wang, Hsin-Ell; Liu, Ren-Shyan; Chen, Jyh-Cheng
Abstract: Introduction: Apoptosis has been suggested as a cytocidal mechanism of the HSV1-tk-expressing cells when exposed to ganciclovir (GCV). This study evaluated the efficacy of 111 In-labeled Annexin V for monitoring tumor responses during prodrug activation gene therapy with HSV1-tk and GCV. Materials and methods: Annexin V was conjugated to DOTA using N-hydroxysulfosuccinimide (sulfo-NHS) and 1-ethyl-3-[3-(dimethylamino)propyl]carbodiimide (EDC), labeled with 111 In-InCl3 and purified using size exclusion chromatography to give 111 In-DOTA-Annexin V conjugate. The radiochemical yield and the radiochemical purity of 111 In-DOTA-Annexin V were 74±12% and 98±3%, respectively ( n =10). 111 In-DOTA-BSA was prepared similarly. An in vitro study to demonstrate the apoptosis of NG4TL4-STK cells after GCV treatment has been performed. Mice bearing NG4TL4-STK and NG4TL4-WT tumors were treated with GCV (10 mg/kg daily) by i.p. injection for 7 consecutive days. Before and during the GCV treatment, biodistribution studies and scintigraphic imaging were performed at 2 h post injection of the radiotracers. Results: The uptake of 111 In-DOTA-Annexin V in treated cells (13.41±1.30%) was 4.1 times higher than that in untreated cells (3.21±0.37%). The GCV-induced cell apoptosis in NG4TL4-STK tumor resulted in a significantly increasing accumulation of 111 In-DOTA-Annexin V (1.92±0.32%ID/g at day 0, 4.79±0.86%ID/g at day 2, 4.56±0.58%ID/g at day 4) was observed, but not for that of 111 In-DOTA-BSA. During consecutive GCV treatment, scintigraphic imaging with 111 In-DOTA-Annexin V revealed high uptake in NG4TL4-STK tumor compared with that in NG4TL4-WT tumor. However, no specific 111 In-DOTA-BSA accumulation in NG4TL4-STK and NG4TL4-WT tumors was observed throughout the course of GCV treatment. Conclusions: This study demonstrated that 111 In-DOTA-Annexin V can be used for monitoring tumor cell apoptosis during prodrug activation gene therapy with HSV1-tk and GCV for cancer treatment. Highlights: Imaging with 111 In-DOTA-Annexin V can detect the apoptosis non-invasively. This modality is useful clinically to assess disease status and therapeutic response. Imaging of cell death will be a unique tool for anti-tumor drug development.